Formation Constants of Chromium(III) Complexes with 8-Hydroxyquinoline and 8-Hydroxyquinoline-5-sulfonic Acid - Suat Aksoy, Mehmet (Asian Journal of Chemistry, 2010)
The complexes of Cr3+ ion formed by 8-hydroxyquinoline (HQ, HL) and 8-hydroxyquinoline-5-sulfonic acid (HQ-5-SA, H2L) were investigated by means of potentiometry and spectroscopy at 25.0 ± 0.1 °C and in ionic strength of 0.1 M KNO3 and 0.1 M KCl, respectively. Over the acidic pH range, the coordination of Cr3+ ion to HQ and HQ-5-SA in 1:1 mole ratios occur, CrL2+ and CrL+ type complexes are formed. At near neutral pH, CrL(OH)+ and CrL(OH) type hydroxo complexes formed. All the data can be explained with the formation of only binary and mixed hydroxo Cr3+ complexes of these ligands. The formation constants were determined using the BEST computer program in 0.1 M KNO3 ionic medium. The stoichiometries of Cr3+ complexes formed with these ligands were defined and their formation constants were determined. Thus, the removing capacities of these ligands could be examined by calculating the equilibrium concentration of Cr3+ that exists in the discharge water of various industries since Cr3+ ions are the main pollutants present during waste water treatment in Bursa city of Turkey.